Hepatitis B (HBsAg) prevalence among obstetric patients in Caluquembe, Angola, 2023–2024 - Anna E. Eberwein; Priscila Ribeiro Cummings; Daniel Cummings; Julia Andre; Kathryn H. Jacobsen (PLoS ONE, 2025)
Objectives Newborns who contract hepatitis B virus (HBV) infections at birth often develop chronic infections that can cause cirrhosis, liver cancer, and death in middle adulthood. Birth doses of hepatitis B vaccine can be lifesaving for babies born to mothers with hepatitis B infections. We aimed to measure hepatitis B prevalence among maternity patients in Huíla, a rural province in southwestern Angola. Methods We conducted a prospective case series study among 317 peripartum women at the Hospital Evangélico de Caluquembe from November 2023 to February 2024. Each participant received a point-of-care hepatitis B surface antigen (HBsAg) test and was asked about HBV and vaccine knowledge. We also conducted qualitative interviews about HBV prevention with 26 healthcare workers. Results The HBsAg prevalence was 4.7%. None of the women who tested positive was previously aware of her status. Only about one-third of the women expressed familiarity with hepatitis B or HBV vaccines, and almost none reported that their older children had received HBV vaccines. Maternal health workers proposed hosting community meetings to provide education about HBV and birth-dose vaccination. Conclusions Only about half of Angolan babies are born at healthcare facilities, but more than 80% of women attend at least one antenatal care visit. Improved access to and uptake of hepatitis B screening at antenatal checkups is essential for ensuring that babies born to women with chronic hepatitis B infections are able to receive birth dose hepatitis B vaccines.